Rare Copy Number Variants Identify Novel Genes in Sporadic Total Anomalous Pulmonary Vein Connection - Shi, Xin; Cheng, Liangping; Jiao, XianTing; Chen, Bo; Li, Zixiong; Liang, Yulai; Liu, Wei; Wang, Jing; Liu, Gang; Xu, Yuejuan; Sun, Jing; Fu, Qihua; et al. (Frontiers in Genetics, 2018)
Total anomalous pulmonary venous connection (TAPVC) is characterized as a rare cyanotic congenital heart defect (CHD). Several genes have been associated with TAPVC but the underlying etiology and mechanisms in most cases remain elusive. To search novel variants and candidate genes, we screened a cohort of 78 TAPVC cases and 100 controls for rare copy number variants (CNV). Then we identified pathogenic CNVs by statistical comparisons between the case and control groups. We identified altogether 8 pathogenic CNVs of 7 candidate genes (PCSK7, RRP7A, SERHL, TARP, TTN, SERHL2, NBPF3). All these 7 genes have not been described previously to be associated with TAPVC. After network analysis of these candidate genes and 27 known pathogenic genes derived from the literature and publicly available database, PCSK7 and TTN had been most strongly linked to TAPVC. Our study provides novel candidate genes potentially related to this rare congenital birth defect that should be further fundamentally researched and discloses the possible molecular pathogenesis of TAPVC.